English L1 VS. L2 Differences in Dissertation Abstracts: Lexical Density, Lexical Diversity and Academic Vocabulary Use - SUSOY, ZAFER (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2023)
This study examines lexical density, lexical diversity and academic vocabulary use in the dissertation abstracts written by EFL (English as a foreign language), ESL (English as a second language) and English L1 (Native Speakers) post graduate students to find out whether these lexical features differ across different English language backgrounds of writers. The data for this study came from a total of 75 dissertation abstracts (n=25 per group) which were about English Language Teaching and related areas. The abstracts were analyzed whereby automated text processing tools and the mean differences were compared between groups with ANOVA and post hoc analysis. A correlation analysis was also computed between the investigated variables. According to the findings, lexical diversity index produced statistically significant differences between EFL and NS groups, however, the subtle mean differences of lexical density and academic vocabulary use were not found significant. On the other hand, the correlations co-efficient scores offered insights into the nature of relationships of the variables in question. The findings are discussed within the framework of idiosyncratic context of ‘abstract genre’.